2018
DOI: 10.3390/nu10111662
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Chemistry, Sources and Bioavailability of Omega-3 Fatty Acids

Abstract: Omega-3 fatty acids, one of the key building blocks of cell membranes, have been of particular interest to scientists for many years. However, only a small group of the most important omega-3 polyunsaturated fatty acids are considered. This full-length review presents a broad and relatively complete cross-section of knowledge about omega-3 monounsaturated fatty acids, polyunsaturates, and an outline of their modifications. This is important because all these subgroups undoubtedly play an important role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(188 citation statements)
references
References 220 publications
(247 reference statements)
4
178
0
6
Order By: Relevance
“…Further analysis of their structure confirmed that these PCs were the main source of the 20:5ω3 and 22:6ω3 fatty acids in the ACS. This difference has been described for other fish products, such as fish oil, where EPA and DHA are primarily linked to TAGs (Cholewski et al, 2018). In the case of the ACS, the omega-3 containing PCs most probably derive from parts of cellular membranes that remain on the graft.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Further analysis of their structure confirmed that these PCs were the main source of the 20:5ω3 and 22:6ω3 fatty acids in the ACS. This difference has been described for other fish products, such as fish oil, where EPA and DHA are primarily linked to TAGs (Cholewski et al, 2018). In the case of the ACS, the omega-3 containing PCs most probably derive from parts of cellular membranes that remain on the graft.…”
Section: Discussionmentioning
confidence: 82%
“…The thickness of fish skin may contribute to its enhanced bacterial barrier properties when compared with thinner biological grafting materials, derived from the lining of internal organs. Perhaps most importantly, cold water fish is known to be rich in omega‐3 polyunsaturated fatty acids (PUFAs; Cholewski, Tomczykowa, & Tomczyk, ; Osman, Jaswir, Khaza'ai, & Hashim, ), and this may contribute to its properties of reducing local inflammation and promoting angiogenesis (Magnusson et al, ), thus supporting wound healing with concomitant pain relief and reduced scarring (Baldursson et al, ; Dorweiler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the production of EPA and DHA from ALA is inconsequential. Making matters worse, omega‐6 PUFAs, which are often overly abundant in the western diet, dampen the conversion of ALA to EPA and DHA . Thus, many experts consider EPA and DHA to be essential fatty acids …”
Section: Residual Riskmentioning
confidence: 99%
“…Making matters worse, omega-6 PUFAs, which are often overly abundant in the western diet, dampen the conversion of ALA to EPA and DHA. 42,43 Thus, many experts consider EPA and DHA to be essential fatty acids. 43 Key dietary sources of EPA and DHA are oily fishes, 42 and several epidemiologic studies have found that groups of people who consume large amounts of such fish have lower rates of CV events and CV death compared with other populations (reviewed in Nishizaki et al 44 ).…”
Section: Epa and Dha: Tg Lowering And Beyondmentioning
confidence: 99%
“…Long-chain PUFA represent an important class of molecules to study in spaceflight, because they shape the basic architecture of the lipid bilayer in all cell membranes. This includes shaping the membrane architecture of neurons, synapses, the retina, and other highly electrically active elements of the brain [3]. It is noteworthy that the dry weight of the human brain is roughly 60% fat with an important dependence upon 20-and 22-carbon long-chain PUFA, especially docosahexaenoic acid (DHA) [4].…”
Section: Introductionmentioning
confidence: 99%